Vestibular Schwannoma with Contralateral Facial Nerve Palsy: A False Localizing Sign - Bhaskar, Mukesh K.; Kumar, Rakesh; Singh, Sunil K.; Meel, M. (Indian Journal of Neurosurgery, 2017)
Vestibular schwannomas are the most common cerebellopontine angle tumors. These tumors commonly present with ipsilateral dysfunction of acoustic, vestibular, trigeminal, and facial nerves. Vestibular schwannoma with involvement of contralateral facial nerve is very unusual, and whenever present, it is considered as a false localizing sign. It seems that displacement and distortion of the brainstem by the large mass lesion may lead to this atypical presentation. We report a case of vestibular schwannoma with contralateral abducens and facial nerve paresis.
Keywords: vestibular schwannoma; facial nerve paresis; false localizing sign